Direct investment and Germany as a business location - Thomas Jost (Deutsche Bundesbank, 1997)
The unfavourable balance of foreign direct investment plays a major role in the ongoing debate on the quality of Germany as a business location. High direct investment outflows and low inflows compared with the United Kingdom and France are often seen as a sign of weakness of Germany as a business location. The relative attractiveness of different countries for foreign direct investment is usually measured in terms of the balance of payments data of the host countries. However, owing to still very divergent recording practices across the industrial countries, such comparisons may be misleading. In this paper it is shown that the statistical errors are minor if investor countries', rather than host countries', data are used to compare the relative attractiveness of different economies for foreign direct investment. Over aperiod of 11 years, foreign balance of payments data show that Germany has received a considerably higher amount of foreign direct investment than is recorded in the German balance of payments. On the outflow side the different data sources give a more homogeneous picture of a persistently heavy commitment of German companies abroad ...
Keywords: 330; Auslandsinvestition; Standortfaktor; Internationaler Wettbewerb; Schätzung; Deutschland